Mecanismos da regulação transcricional de Rasgef1b, um gene induzível por receptores do tipo Toll - Felipe Batista Leão (2019)
The guanine-nucleotide exchange factor RasGEF1b is encoded by a gene whose expression is induced in innate immune cells in response to the activation of Toll-like receptors (TLRs). Its mRNA accumulates in human and mouse macrophages upon stimulation with various TLRs agonists as well as in mice infected with protozoan parasites, suggesting that Rasgef1b plays a role in innate immunity. However, its role in this context is not yet fully understood. In addition, the transcriptional mechanisms that regulate its expression are still unknown due to the lack of studies about the promoter and the potential regulatory elements involved in this process. As the diverse biological functions mediated by the RasGEF/RasGTPases modules are in part dependent on their expression profile in specific cell types or tissues, understanding the transcriptional mechanisms that drive their directed expression can provide important information about their role in the cell. Therefore, our objective here was to characterize the promoter region that regulates the TLR-inducible Rasgef1b expression. For this, we cloned a 2.8 kb sequence (-2747/+119) upstream from Rasgef1b coding region in the luciferase reporter plasmid pGL3-basic. Progressive 5’ and 3’ deletions were performed and the activity of each construct was assessed by transient transfection and reporter gene assay. Our results show that a short proximal sequence containing 302 bp (-183/+119) is sufficient and necessary to efficiently promote luciferase expression in HEK293 cells and Raw264.7 macrophages, exhibiting robust basal and TLR-induced activity. Therefore, we provide direct evidence that this region harbors Rasgef1b active promoter. Interestingly, we have identified that the sequence is evolutionarily conserved, contained in an accessible chromatin region with a CpG island, appears to constitutively recruit the RNA Polymerase II, and harbors essentially Sp1 and TLR-inducible NF-kB binding sites. We showed that the overexpression of NF-κB RelA or cRel subunits, but not of RelB complexes, induced a significant increase in promoter activity, and that mutation of the kB sites located upstream or downstream from Rasgef1b TSS resulted in a significant reduction in the LPS-inducible promoter activation in mouse macrophages. In addition, we showed through electrophoretic mobility shift assays (EMSA) that some of the kB elements can recruit NF-kB dimers, and through ChIP-seq, we showed that RelA is recruited not only to Rasgef1b promoter, but also to additional distal regions. Finally, we found that the TLR-inducible Rasgef1b expression is reduced in RelA deficient or Bay11-7082-treated macrophages, indicating that its expression is partially dependent on NF-κB. Altogether, we report for the first time the identification and functional characterization of Rasgef1b promoter, demonstrating the contribution of NF-κB in its TLR-inducible expression.